2017
DOI: 10.3892/etm.2017.5674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic efficacy between ultrasound elastography and magnetic resonance imaging for breast masses

Abstract: Abstract. The present study compared the efficacy of ultrasound elastography (UE), magnetic resonance imaging (MRI) and the combination of the two methods (UE+MRI) in the differential diagnosis of benign and malignant breast tumors. In total, 86 patients with breast masses were recruited and evaluated by UE, MRI and UE+MRI. Strain ratios of UE were calculated for the breast mass and adjacent normal tissues. In addition, the receiver operating characteristic (ROC) curve was obtained, while the sensitivity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Our results do not support an additional beneit of SWE when used in conjunction with both US and MRI. his is in contrast to studies in breast lesions where SWE and MRI combined outperformed MRI alone (23). It seems that SWE is potentially another variable that cannot be speciic for malignancy in soft-tissue tumors.…”
Section: Discussionmentioning
confidence: 70%
“…Our results do not support an additional beneit of SWE when used in conjunction with both US and MRI. his is in contrast to studies in breast lesions where SWE and MRI combined outperformed MRI alone (23). It seems that SWE is potentially another variable that cannot be speciic for malignancy in soft-tissue tumors.…”
Section: Discussionmentioning
confidence: 70%
“…Strain elastography with SR has been compared to evaluation using a strain histogram with similar good results [7]. SR was reported to be better than magnetic resonance imaging (MRI) for breast tumor characterization, but the combination of the two modalities had a better ROC-AUC of 0.914 [8]. Furthermore, for the evaluation of axillary lymph nodes in breast cancer patients, a combined evaluation of B-mode ultrasound (US) and Real-Time Elastography (RTE) increased specificity [9].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Parajuly et al [30] , reported a higher sensitivity and specificity of conventional USG (91.8% and 84.8%). In another study, study Cheng et al found that USG elastography performed better than MRI in terms of diagnostic accuracy (82.5% as compared to 75.4%) [31] .…”
Section: Discussionmentioning
confidence: 92%